Preparation of Oil Palm Leaves Ash-Supported Titania for the Elimination of Safranin-O Dye in Water - Yudha S, Salprima; Adfa, Morina; Istiqphara, Swadexi; Falahudin, Aswin; Reagen, Muhamad Alvin (Universitas Jenderal Soedirman, 2024)
ABSTACT. The objective of this study was to develop an approach for incorporating titanium oxide or titania into oil palm leaves ash (OPLA) using a simple procedure. The study process comprised the mixing of oil palm leaves (OPL) powder and titanium tetraisopropoxide in chloroform solvent, followed by the elimination of the solvent to obtain a solid residue. Subsequently, the residue obtained was calcined at 500 °C for 5 hours, leading to the production of a yellow-light powder. The results of product characterization using X-ray diffraction (XRD) and scanning electron microscopy analysis showed the presence of titanium oxide in OPLA. In addition, the wide diffractogram detected in XRD analysis revealed the presence of a silica peak. The un-sharp peaks in the regions of 25.6°, 38.2°, 47.9°, 54.5°, and 62.9° showed that the TiO2 particles were pure anatase, and no peaks of other TiO2-anatase phases were detected. Analysis using SEM showed that the surface of the material obtained was irregular and tended to have a hollow shape, while energy dispersive X-ray analysis revealed a SiO2 content of approximately 73%. However, the titanium element or titania was not detected possibly due to its small concentration. The material obtained also had a good catalytic activity for safranin-O dye elimination under sunlight irradiation, which served as the activation energy source. Based on these findings, the use of OPLA (a side product of oil palm plantations) could be evaluated economically due to its effective role in the catalytic process despite the addition of a small amount of titania catalyst. Keywords: Oil palm leaves ash, titania, safranin-O, sunlight irradiation.